Playing on the Periphery - Brabazon, Tara (Sport in the Global Society, 2006)
Part of the Sport in the Global Society series, this innovative and creative text explores collective history, memory, and sport culture, tracking the passage of sports away from England. The author investigates why 'elite' Eng sports - such as rugby and cricket - became national sports in New Zealand and Australia, and asks why 'working class' Eng sports - such as football - have travelled less well to these areas. Focusing on these sports, the author tracks narratives and myths, tracing the passage of colonial truths, behaviours and practices. Clearly defined sections in the book focus on: * sport and tourism * sport and history * sport and memory. Using a refreshingly broad range of sources to analyze differences between popular culture and sporting memory, this book offers new perspectives on sport and makes an interesting reference for masters and postgraduate readers in sport and cultural studies.